The identity of Chelodina oblonga Gray 1841 (Testudines: Chelidae) reassessed - Shea, Glenn; Thomson, Scott; Georges, Arthur (Zootaxa, 2020)
The identity of Chelodina oblonga has been unclear because it has been variously defined to include populations of snake-necked chelid turtle from the southwest of Western Australia, across northern Australia, Cape York and southern New Guinea in its broadest conception, from just the northern part of this range (northern Australia and New Guinea), or restricted to the southwest corner of Western Australia in its narrowest conception. Uncertainty over the identity of the type specimens has added to the confusion. In this paper, we review the historical data on the extent of the type series of Chelodina oblonga, and its potential provenance, and find evidence that resolves some of the inconsistencies in previous literature on the identification of the type. Our analysis casts doubt on the northern Australian provenance of the type material. Hence, we return the name C. oblonga to the south-western species, in accordance with the genetic evidence for the provenance of the type in the Natural History Museum, London, and the external morphology of the type series. We designate a lectotype for the species, and redefine the subgeneric names that apply to the Australasian genus Chelodina, providing a new subgeneric name for one lineage.